Predictive Value of an Age-Based Modification of the National Early Warning System in Hospitalized Patients With COVID-19. (10th August 2021) - Maves, Ryan C; Richard, Stephanie A; Lindholm, David A; Epsi, Nusrat; Larson, Derek T; Conlon, Christian; Everson, Kyle; Lis, Steffen; Blair, Paul W; Chi, Sharon; Ganesan, Anuradha; Pollett, Simon; et al.
Abstract: Background: Early recognition of high-risk patients with coronavirus disease 2019 (COVID-19) may improve outcomes. Although many predictive scoring systems exist, their complexity may limit utility in COVID-19. We assessed the prognostic performance of the National Early Warning Score (NEWS) and an age-based modification (NEWS+age) among hospitalized COVID-19 patients enrolled in a prospective, multicenter US Military Health System (MHS) observational cohort study. Methods: Hospitalized adults with confirmed COVID-19 not requiring invasive mechanical ventilation at admission and with a baseline NEWS were included. We analyzed each scoring system's ability to predict key clinical outcomes, including progression to invasive ventilation or death, stratified by baseline severity (low [0–3], medium [4–6], and high [≥7]). Results: Among 184 included participants, those with low baseline NEWS had significantly shorter hospitalizations ( P < .01) and lower maximum illness severity ( P < .001). Most (80.2%) of low NEWS vs 15.8% of high NEWS participants required no or at most low-flow oxygen supplementation. Low NEWS (≤3) had a negative predictive value of 97.2% for progression to invasive ventilation or death; a high NEWS (≥7) had high specificity (93.1%) but low positive predictive value (42.1%) for such progression. NEWS+age performed similarly to NEWS at predicting invasive ventilation or death (NEWS+age: area under the receiver operating characteristics curve [AUROC], 0.69; 95% CI, 0.65–0.73; NEWS: AUROC, 0.70; 95% CI, 0.66–0.75). Conclusions: NEWS and NEWS+age showed similar test characteristics in an MHS COVID-19 cohort. Notably, low baseline scores had an excellent negative predictive value. Given their easy applicability, these scoring systems may be useful in resource-limited settings to identify COVID-19 patients who are unlikely to progress to critical illness.